2012
DOI: 10.1596/1813-9450-6064
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in Culture and Corruption: A Review

Abstract: The Impact Evaluation Series has been established in recognition of the importance of impact evaluation studies for World Bank operations and for development in general. The series serves as a vehicle for the dissemination of findings of those studies. Papers in this series are part of the Bank's Policy Research Working Paper Series. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 76 publications
1
39
0
8
Order By: Relevance
“…For the purpose of this exercise, we present the following analysis at the individual level since our study was not explicitly designed to study gender effects at the group level.15 Here, we are more interested in within-gender differences across different institutional environments, rather than between-gender differences within the same institutional settings. In terms of level differences, our findings are in line with existing research suggesting that males are generally more prone to risky behavior and, often as a consequence thereof, engage in illicit behavior more often and to a larger extent than females (cf Torgler and Valev, 2010;Banuri and Eckel, 2012)…”
supporting
confidence: 91%
See 1 more Smart Citation
“…For the purpose of this exercise, we present the following analysis at the individual level since our study was not explicitly designed to study gender effects at the group level.15 Here, we are more interested in within-gender differences across different institutional environments, rather than between-gender differences within the same institutional settings. In terms of level differences, our findings are in line with existing research suggesting that males are generally more prone to risky behavior and, often as a consequence thereof, engage in illicit behavior more often and to a larger extent than females (cf Torgler and Valev, 2010;Banuri and Eckel, 2012)…”
supporting
confidence: 91%
“…While most of the economic research on corruption and tax evasion has focused on the deterrence of income tax evasion or its related variants, other forms of tax evasion where taxes are in some way collected through a third party have received little attention; trade, import or custom tax evasion is one such example, as taxes, in the form of custom duties, are collected not by a national revenue service, but by an intermediary customs or duties officer (Banuri and Eckel, 2012). This is particularly true for the case of "corruption within tax evasion."…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers have emphasized the importance of cultural correlates. Culture was found to affect people's behavior and informal norms as well as policies on corruption, legal regulation, and punishment for corrupt behavior (Benuri & Eckel, 2012). Cross-cultural studies found that wealthier countries that have larger governments (a measure of a government's general final consumption expenditure as a percent of the country's GDP) and that value individual autonomy and social diversity tend to be less corrupt (O'Connor & Fischer, 2012).…”
Section: Correlates Of Corruptionmentioning
confidence: 99%
“…Hauk and Saez-Marti (2001) argue that small-scale corruption is not necessarily considered negative in public opinion. Banuri and Eckel (2012) state that corruption norms constitute specific types of social norms and determine the expectations of individuals on the extent of corruption. Cameron et al (2009) analyse corruption behaviour and attitudes of students from low-corruption countries (Australia and Singapore) and from high-corruption countries (India and Indonesia).…”
Section: Corruption and Social Normsmentioning
confidence: 99%